POLÍTICAS PÚBLICAS EM EDUCAÇÃO FÍSICA: UMA ANÁLISE DO ESPORTE EDUCACIONAL NA FUNDAÇÃO MUNICIPAL DE ESPORTE (FUNESP) - Anderson Volpato de Paiva (2023)
This dissertation is linked to the Line of Research: History, Policies and Education of the Graduate Program in Education at UFMS. The research aims to analyze the configuration, financing and social control in the Public Policies of Physical Education, sport and leisure of the Municipal Sports Foundation (Funesp), in the city of Campo Grande-MS, with emphasis on educational sport. A descriptive method was used, with a qualitative approach and data collection in two stages: in the first, a documental analysis was carried out at Funesp and in the second, semi-structured interviews were carried out with 6 managers who work and/or worked in the institution. The data were analyzed based on the inspiration in the critical-dialectical framework. As for the emphasis on educational sport in the main documents and legislation that support the Public Policies on Physical Education, sport and leisure developed by Funesp, the main results showed that despite the attempt to promote actions in the educational dimension, there is still a gap between the legal apparatus and the materialization of access to the right to educational sport as a priority. As for the configuration and scope, based on the analysis of the main documents, it is possible to note the recognition of sport and leisure as an individual, collective and social right. We also observed that the programs and criteria for permanence present the universalization category, however, it is not possible to state that the analyzed policy is universal, since the reach is low, according to the percentage reached in relation to the population of Campo Grande- MS.It was found that there are mechanisms for political articulation at Funesp, that is, it shows signs of intersectoriality. In the study of the configuration of Funesp's financing with regard to the sources, direction and magnitude of expenditures, we verified that despite the Campo-Grandense de Esportes e Lazer (SICEL) presenting and bringing a proposal for a very broad financing policy, Funesp finds limits in terms of sources, at this time in short the main source of funding is the Annual Budget Law and we highlight the challenges of a robust budget that guarantees subsidy for its actions. In the analysis of participation and social control of public policies in Physical Education, Sport and Leisure developed by Funesp, given the information collected, we identified the interest in discussions on participation and social control in the management of public policies within the analyzed period. This participation and social control can be seen in the construction of SICEL, in the conferences, in the construction of PLAMEL, in the municipal sports and leisure council and in the management groups of sports and leisure facilities. From these observations, it is essential to produce content to deepen and advance discussions on the object.From these observations, it is concluded that SICEL, despite some limitations pointed out, in its movement proposes advances in the configuration of the scope, financing and social control in the scenario of Public Policies of Physical Education, Sport and Leisure of Funesp in the municipality of Campo Grande/MS.